2016
DOI: 10.1080/21599165.2016.1231669
|View full text |Cite
|
Sign up to set email alerts
|

The Arctic in the political discourse of Russian leaders: the national pride and economic ambitions

Abstract: This article explores how Arctic policy is presented in Russian political narratives. This is achieved through the discourse analysis of 109 official documents published within seven-year timeframe (2008-2015) on the official website of the Russian President. The article argues that Russian leaders emphasise the state's geographical location and significant contribution to historical exploration and environmental protection of the region to frame Russia as an 'Arctic Great Power' which has natural rights to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…Furthermore, the goal of the Arctic Days, which emphasizes Russian Arctic exceptionalism, is in line with how Russian leaders use references to historical and cultural presence in the region as an identity-building mechanism to justify proactive (often resourcedemanding) Arctic policies. 46 Accordingly, the utilization of the above-mentioned arenas by the Russian government can be considered a means for the powerful state to assert its dominance, control the agenda, and catalyze outcomes to its benefit.…”
Section: Conferences Established 2010-2013mentioning
confidence: 99%
“…Furthermore, the goal of the Arctic Days, which emphasizes Russian Arctic exceptionalism, is in line with how Russian leaders use references to historical and cultural presence in the region as an identity-building mechanism to justify proactive (often resourcedemanding) Arctic policies. 46 Accordingly, the utilization of the above-mentioned arenas by the Russian government can be considered a means for the powerful state to assert its dominance, control the agenda, and catalyze outcomes to its benefit.…”
Section: Conferences Established 2010-2013mentioning
confidence: 99%
“…Если в XIX -начале XX в. преобладала риторика экзотизации, индигенизации Арктики, утверждения ее как неизведанной, опасной или «пустой» периферии империй (Ryall, Shimanski, Waerp 2010), то для XX в. характерна также политизация Арктики, включение ее в контекст территориальных споров и практик государственного управления территорией. Так, согласно (Khrushcheva, Poberezhskaya 2016) в России динамика образа Арктики характеризовалась несколько хаотичной эволюцией от имперского поиска новых земель и ресурсов (прирастания богатств) к героическому завоеванию Арктики, приручению и модернизации (советизации) пространства при помощи технологий в первые советские десятилетия, далее -к идее кратчайшего расстояния между СССР и США в период холодной войны, затем -к отсутствию сфокусированного интереса в первое постсоветское десятилетие и, наконец, к возвращению Арктики в официальный дискурс в начале XXI в.…”
Section: концептуализация арктики как особого региона: глобальный и рunclassified
“…Вместе с этими идеями Россия, впрочем, усвоила и общие для глобальной Арктики противоречия, например, с одной стороны, уместность не милитаризации Арктики, но международной кооперации арктических стран, с другой стороны, важность для каждой страны декларации суверенных прав в Арктике. По мнению О. Хрущевой и М. Побережской, в начале XXI в. российский арктический нарратив формировался официальными представителями государства на основе: идей «Arctic State» -легитимации статуса арктического государства через географическое положение, историю освоения, наличие коренного арктического населения среди граждан России; проведения экологических акций; усиления «национальной безопасности» и укрепления границ; разработки углеводородной базы и перспектив СМП как международной морской трассы (Khrushcheva, Poberezhskaya 2016; см. об этом также: Киселёв, Назукина 2016: 145-152).…”
Section: концептуализация арктики как особого региона: глобальный и рunclassified
“…Gritsenko (2016) demonstrated that hydrocarbon energy development has dominated the Russian Arctic policy agenda mediated through the mainstream Russian media outlets during 2011-15. Khrushcheva and Poberezhskaya (2016) argued that Russian leaders use symbolic means to frame Russia's Arctic policy to the Russian public in order to justify Russia's claim to the Arctic region and the development of abundant Arctic resources.…”
Section: Introductionmentioning
confidence: 99%